Analisis hukum Islam terhadap praktik menabung emas melalui platform digital dalam perspektif fiqh kontemporer - Diana, Zuhur; Isroqunnajah, Isroqunnajah (Maliki Interdisciplinary Journal, 2025)
In the era of economic digitalization, saving gold through digital platforms has become an investment that is popular with the public, especially the younger generation. The attraction of this investment lies in the ease of access, flexible savings nominal, and practical transaction features. However, this practice also raises new problems from an Islamic legal perspective, especially regarding the validity of contracts, ownership status and clarity of transaction procedures. This research aims to analyze the law of saving gold through digital platforms from a contemporary fiqh perspective. Researchers used qualitative methods with a normative legal approach to various book literature, journal articles, DSN-MUI fatwas, and goverment regulations that were relevant to the research topic. The research results show that there are differences of opinion among ulama regarding the practice of saving gold via digital platforms. Some scholars forbid it because they consider gold to be wait (a medium of exchange) which must be transacted in cash, while other scholars allow it because gold is valued as sil'ah (goods) that can be traded. As for the development of contemporary fiqh, the practice of digital gold savings can be permitted if it meets sharia principles such as clarity of contract, legal ownership status, taqabudh (handover), at-tamatsul (equivalent), as well as avoiding usury (interest), gharar (vagueness), and maysir (speculation). Thus, there is a need for continuous education for the public and transparency from digital savings service providers in order to maintain trust and conformity to Islamic muamalah principles.